Vegetative Propagation and Forest Tree Improvement - Rao, H. S. (Indian Forester, 1953)
In tree improvement work we seek to recognize desirable individuals in nature, multiply them as such vegetatively, while at the same time attempt to combine useful traits of different individuals into a synthetic hybrid. The resulting improved hybrid may further have to be clonally multiplied to preserve its complex genetic make-up. Even when a good genotype has been found which produces seed of dependable heredity, it may have to be vegetatively multiplied and grown in compact seed orchards. Scions of such individuals will have to be budded or grafted on wild stock for this purpose. Thus at all stages vegetative propagation is an invaluable aid. The speed and success of tree improvement for large-scale afforestation depends on vegetative multiplication in a large measure. Tree species vary in their ability to regenerate vegetatively, namely, through cuttings, layers, budding or grafting. On a scrutiny of the Indian forest species it was found that no less than 74 species reproduce by cuttings, 11 by layers, 9 by grafting or budding, and 104 by root-suckers, which shows the scope there is for selection and multiplication of good phenotypes or genotypes. Coppicing ability is also an indication of the faculty for vegetative reproduction. There are no less than 161 species which coppice more or less vigorously. With the aid of hormones many of them may be induced to root. Hormones might also be employed to increase greatly the percentage success of those which normally strike root. Thus, intensive vegetative propagation promises wonderful possibilities of forest tree improvement.